Interlaboratory Oral Anticoagulant Quality Assessment by the Netherlands Federation of Thrombosis Services - van Dijk-Wierda, C. A; Hermans, J; Loeliger, E. A; Roos, J (Thrombosis and Haemostasis, 1977)
The 50 laboratories of the Netherlands Federation of Thrombosis Services, covering a population of 9 million and responsible for the laboratory control of approximately 150,000 patients under oral anticoagulation, have participated since 1974 in a voluntary external and internal quality control program. The external program comprises a monthly distribution to the member laboratories of a series of artificially prepared control blood samples, two of which are identical. The overall variation of the coagulation times found were 10% (CV) in 1974 and 8% (CV) in 1975. Performance improved rather abruptly at the beginning of 1975, after the application of a tight methodological standardization and improvement by the manufacturer of the thromboplastin preparation (Thrombotest) used by the great majority of the laboratories involved. The main source of variation was found to be random error in the Thrombotest determination, approximating 6%. Interbatch variation of Thrombotest and inter-aliquot variation of control blood samples both do amount to approximately 3% (CV). In terms of rabbit tissue thromboplastins, which have a lower sensitivity than Thrombotest (i. e., a flatter slope of the correlation between the PT and the anticoagulant effect), the total variation in the performance of the Dutch laboratories is 2.2-5.6% (CV), which is unusually low. The main reason for this is the fact that the laboratories can rely not only on the services of the manufacturer but also on a central information office and a reference laboratory responsible for the preparation of the control blood as well as the standardization (calibration) of thromboplastin.